To What Extent Do Nurses Use Clinical Trials in Their Practice? - Salam Bani Hani; Abdulqadir J. Nashwan (Babali Nursing Research, 2022)
Due to the growing global need for clinical trials, the number of nurses working as research nurses or research coordinators has increased during the last two decades. This paper discusses the potential role and contribution of nurses in conducting high-utility nursing clinical trials. More work is still needed to optimize the knowledge and skills of nurses working in the field of clinical trials.